Behavioral Symptoms May Correlate With the Load and Spatial Location of Tubers and With Radial Migration Lines in Tuberous Sclerosis Complex - Cohen, Rony; Genizi, Jacob; Korenrich, Liora (Frontiers in Neurology, 2021)
Objective: Tuberous sclerosis complex (TSC) is a multisystem neurocutaneous genetic disorder. The clinical manifestations are extensive and include neurological, dermatological, cardiac, ophthalmic, nephrological, and neuropsychiatric manifestations. The prediction and pathophysiology of neuropsychiatric disorders such as emotional symptoms, conduct problems, hyperactivity, and poor social behavior are poorly understood. The aim of the study was to diagnose neuropsychiatric symptoms in individuals with TSC, and to examine their possible correlations with quantity, magnitude, and spatial location of tubers and radial migration (RM) lines. Methods: The cohort comprised 16 individuals with TSC, aged 5-29 years, with normal or low normal intelligence. The participants or their parents were requested to fill Strengths and Difficulties Questionnaire (SDQ) and the TAND (TSC-associated neuropsychiatric disorders) Checklist for assessment of their neuropsychiatric symptoms. Correlations were examined between these symptoms and the magnitude, quantities, and locations of tubers and white matter RM lines, as identified in T2/FLAIR brain MRI scans. Results: The SDQ score for peer relationship problems showed correlation with the tuber load (r=0.52, p<0.05). Tuber load and learning difficulties correlated significantly in the temporal and parietal area. Mood swings correlated with tubers in the parietal area (r=0.529, p<0.05). RM lines in the temporal area correlated with abnormal total SDQ (r=0.51, p<0.05). Anxiety and extreme shyness were correlated with RM lines in the parietal area, r=0.513, p<0.05 and r=0.593, p<0.05, respectively. Hyperactive/inattention correlated negatively with RM lines in the parietal area (r=-707, p<0.01). Conclusions: These observations may lead to future studies for precise localization of neuropsychiatric symptoms, thereby facilitating directed therapy.